2009
DOI: 10.2136/sssaj2008.0213
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Reflectance Spectroscopy Prediction of Soil Properties: Effects of Sample Cups and Preparation

Abstract: Most methods for soil analysis are based on wet chemistry. Near infrared reflectance spectroscopy (NIRS) is a cost‐effective and environmentally sound alternative technique. This study evaluated the effect of sample fineness (0.2, 0.5, 1, and 2 mm) and sample cups (transport versus spinning) on the accuracy of NIRS predictions of soil texture, cation‐exchange capacity, pH, total C and N, organic C, and potentially mineralizable N (Nmin) using 150 air‐dried samples collected from a 15‐ha site dominated by Humaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 37 publications
4
49
0
5
Order By: Relevance
“…This agrees with the findings of Uldelhoven et al (2003) and Nduwamungu et al (2009b) who reported that the prediction of soil properties without a theoretical basis for NIRS calibration (i.e., secondary properties; P, K, Cu, Zn, and Mn) was generally less reliable compared with the prediction of primary properties. The difference is probably related to the correlation of the reference methods to near-infrared reflectance spectra.…”
Section: Assessment Of the Performance Of Nirs Predictionssupporting
confidence: 92%
“…This agrees with the findings of Uldelhoven et al (2003) and Nduwamungu et al (2009b) who reported that the prediction of soil properties without a theoretical basis for NIRS calibration (i.e., secondary properties; P, K, Cu, Zn, and Mn) was generally less reliable compared with the prediction of primary properties. The difference is probably related to the correlation of the reference methods to near-infrared reflectance spectra.…”
Section: Assessment Of the Performance Of Nirs Predictionssupporting
confidence: 92%
“…Previous studies have suggested that models with R 2 > 0.8 provide acceptable or high accuracy levels for the prediction of soil properties whereas models with R 2 < 0.8 but > 0.6 provide only medium level predictions (e.g., Chang et al, 2001;Malley et al, 2004;Nduwamungu et al, 2009). In the present study, we adopted this classification into different R 2 classes and advise that the evaluation of the usefulness of a predictive model should be determined by the amount of uncertainty reduction it provides for a given purpose.…”
Section: Chemometric Analysesmentioning
confidence: 99%
“…Among the factors that could result in obtaining different results between studies the origin of the samples (i.e., different geographical and agro-ecological regions), preparation of the samples (i.e., particle size) and calibration procedures are mentioned (Nduwamungu et al, 2009a;2009b). Volkan-Bilgili et al (2010) reported that, the best prediction models were obtained for organic matter (R 2 = 0.80), total carbonates (R NCal, número de muestras de calibración; F= finos (<0.5 mm); G= gruesos (<2 mm); min, mínimo; max, máximo; DS= desviación estándar; CV= coeficiente de variación [(DS/media) x 100].…”
Section: Resultsmentioning
confidence: 99%
“…Entre los factores que pudieran resultar en la obtención de diferentes resultados entre los estudios se mencionan la procedencia de las muestras (i.e., diferentes regiones geográficas y agroecológicas), la preparación de las muestras (i.e., tamaño de partícula) y los procedimientos de calibración (Nduwamungu et al, 2009a;2009b). Volkan-Bilgili et al (2010) reportaron que los mejores modelos de predicción que obtuvieron fueron para materia orgánica (R (2006) presentan una excelente revisión de literatura la cual muestra el potencial del análisis cuantitativo por infrarrojo.…”
Section: Resultsunclassified